The crucial role of lateral root angle in enhancing drought resilience in cotton - Guo, Congcong; Bao, Xiaoyuan; Sun, Hongchun; Chen, Jing; Zhu, Lingxiao; Zhang, Jianhong; Zhang, Haina; Zhang, Yongjiang; Zhang, Ke; Bai, Zhiying; Li, Anchang; Liu, Liantao; et al. (Frontiers in Plant Science, 2024)
Plant responses to drought stress are influenced by various factors, including the lateral root angle (LRA), stomatal regulation, canopy temperature, transpiration rate and yield. However, there is a lack of research that quantifies their interactions, especially among different cotton varieties. This experiment included two water treatments: well-watered (75 ± 5% soil relative water content) and drought stress (50 ± 5% soil relative water content) starting from the three-leaf growth stage. The results revealed that different LRA varieties show genetic variation under drought stress.Among them, varieties with smaller root angles show greater drought tolerance.Varieties with smaller LRAs had significantly increased stomatal opening by 15% to 43%, transpiration rate by 61.24% and 62.00%, aboveground biomass by 54% to 64%, and increased seed cotton yield by 76% to 79%, and decreased canopy temperature by 9% to 12% under drought stress compared to the larger LRAs. Varieties with smaller LRAs had less yield loss under drought stress, which may be due to enhanced access to deeper soil water, compensating for heightened stomatal opening and elevated transpiration rates. The increase in transpiration rate promotes heat dissipation from leaves, thereby reducing leaf temperature and protecting leaves from damage.Demonstrating the advantages conferred by the development of a smaller LRA under drought stress conditions holds value in enhancing cotton's resilience and promoting its sustainable adaptation to abiotic stressors.